The impact of brand love on brand loyalty with self-esteem and social-influence as a mediating role: Indonesian photography industries - Kamaaluddin, Kamaaluddin; Ramadania, Ramadania; Heriyadi, Heriyadi; Pebrianti, Wenny; Ahmadi, Ahmadi (Journal of Management and Digital Business, 2025)
In today's digital age, the photography industry is experiencing rapid growth, fueled by increasing public interest in photography, advancing camera technology, and social media's influence. Along with the increased competition among photography companies as a result of this growth, it is essential to recognize the elements influencing brand loyalty. This study examines how Brand Love influences Brand Loyalty in Indonesia's photography industry, with self-esteem and social influence as mediating variables. The research employs a quantitative approach, gathering data from photographers and photography enthusiasts in Indonesia. The study analyzes the relationships between variables using Structural Equation Modeling (SEM) with SmartPLS Version 4.0. The results show that Brand Love significantly improves Brand Loyalty and that this link is mediated by  social-influence and self-esteem. This research contributes valuable insights into brand dynamics within the photography industry and provides practical recommendations for marketers seeking to enhance brand loyalty in a competitive market environment.